Parameter optimization of the notched blade spiral fertilizer discharger for pineapple orchards based on DEM - Dun, Guoqiang; Sheng, Quanbao; Ji, Xinxin; Li, Hailiang; Ma, Chunyu; Li, Xinming; Sun, Haitian; Wang, Luhan; Ma, Chao; Yu, Zhenzhen; Wang, Hongxuan (Frontiers in Mechanical Engineering, 2025)
IntroductionIn order to improve the fertilizer-discharging uniformity of the traditional spiral fertilizer distributor and achieve precise and controllable fertilization, based on the agronomic characteristics of fertilization in pineapple orchards, a notched-blade spiral fertilizer discharger with the mechanism of discontinuous-blade sliding-cutting and pushing-pore fertilization is innovatively designed.MethodsBased on parametric modelling and determining the volume of fertilizer accommodation of the spiral, the theoretical fertilizer-discharging amount of the fertilizer discharger is determined in combination with theoretical analysis. The main factors influencing the fertilization performance of the spiral fertilizer discharger are analyzed using theoretical calculation formulas. The discrete element method is used to simulate the fertilizer-discharging process. By comparing simulation experiments, it is determined that the notched-blade spiral fertilizer discharger has better uniformity than the traditional one. The effects of the number and shape of periodic notched blades on the fertilizer-discharging uniformity are analyzed through single-factor experiments. The L9 (3⁴) orthogonal table is adopted for conducting orthogonal simulation tests.ResultsThe test results show that the primary and secondary order of the influence of test factors on test indexes is blade notch shape and periodic blade notch number. When the blade notch is a sector, and the periodic blade has three notches, the fluctuation coefficient of fertilizer discharge uniformity is 27.01%. The results of the bench test show that the uniformity fluctuation coefficient of the notched blade spiral fertilizer discharger is 27.42% when the rotating speed is 60r/min. The experimental and simulation values are consistent. Moreover, the fluctuation coefficient of the spiral fertilizer discharger is reduced by 64.86 percentage points compared with that of the spiral fertilizer discharger under the same conditions. Moreover, the fluctuation coefficient of the notched blade spiral is 64.86% lower than that of the spiral fertilizer discharger under the same conditions. Based on different rotational speeds, the fitting curve of fertilizer discharge is y = 2.02x + 23.02.ConclusionThe fertilizer discharge can be controlled by adjusting the rotating speed. It improves the controlled accuracy and uniformity of fertilizer application and achieves the goal of green and sustainable development of the pineapple industry in the tropics. The research results can provide a reference for designing and optimizing spiral fertilizer dischargers.